Managing Homme Appliances and Security System Using GSM Technology (International Journal of Psychosocial Rehabilitation, 2020)
This examination work explores the capability of 'full home control and security,' which is the point of the home automation systems in the not-so-distant future. In our day-to-day lives, sometimes we forget to switch off some of the home appliances like fans, lights, ACs, etc. This causes a lot of electricity wastage. In order to save electricity and time for human beings, we implement this project. The main aim of the paper is that we can handle the home appliances by using the GSM mobile phone, and just by sending SMS to turn ON/OFF, he/she can control the home appliances, and also in this paper we are providing the surveillance camera for security reasons. For persons who are handicapped and disabled, this artificial intelligence-based home automation is very helpful. This application can be used wherever you are in the country.